Więzi w dynamicznych sieciach międzyorganizacyjnych - przypadek więzi relatywnych - Niemczyk, Jerzy (Relations in interorganizational networks - case of the relative relations, 2006)
The work concerns on relations in interorganizational networks, particularly relative relations. Its main goal is the identification of those relative relations characteristics, which would enable to identify, describe and understand. Based on this knowledge, the proposals of research methods enabling to analyze the relative relations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 124-132